PENGARUH PENERAPAN MODEL NUMBERED HEADS TOGETHERTERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKAPESERTA DIDIK KELAS VII - Pitriati - (Departemen Matematika, 2019)
The purpose of learning mathematics is very important is to develop the ability to understand mathematical concepts so as to create learning activities that are fun and well understood by students. Reality in the field, learning is still teacher-centered, causing low activity, competitiveness and lack of ability to understand students' concepts in working on mathematical questions given. In this case, so that an understanding of mathematical concepts can be achieved requires a learning model that can make students more focused and interested in learning, thus making them play an active role in each learning activity. The learning model used is the Numbered Heads Together (NHT) learning model which can provide opportunities for students to be active in learning so that the process of learning is student-centered. The purpose of this study was to describe the increase in students' understanding of mathematical concepts during and after learning using the Numbered Heads Together learning model in class VII.5 of SMP Negeri 30 Padang Academic Year 2018/2019. The type of research is classroom action research. The instruments used were in the form of observation sheets and performance assessment sheets. The subjects of this study were class VII.5 students of SMP Negeri 30 Padang who had the ability to understand mathematical concepts that were still low. The research data were analyzed by descriptive statistics. Based on the data analysis, the results of the study were obtained, namely: through the NHT type cooperative learning model can improve the understanding of the mathematical concepts of Class VII.5 students N Padang Middle School 30, Academic Year 2018/2019. This is indicated by the average concept understanding test results in the first cycle of 61.87 with classical completeness of 31.25% increasing in the second cycle on average to 67.34 with classical completeness of 34.38%.Keywords - numbered heads together model, direct learning model, ability to understand mathematical concepts